ADAPTASI STRATEGI MENGAJAR GURU TERHADAP VARIASI RESPONS BELAJAR SISWA DI SEKOLAH DASAR - Norianti Pai Tiba; Meti Lakapu, Yori Tafuli, Yanti Djo, Bonita Lona, Stiven Sanang, Mehelia Tenis, Nofrianti Humau, Kar (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
An unavoidable reality during the learning process is the variation in abilities, learning styles, motivations, and levels of student engagement in elementary schools. This is a difference in the way elementary school students learn. This situation requires teachers to be able to adapt learning strategies flexibly, effectively, and meaningfully. The purpose of this study is to analyze how teachers adapt learning strategies to the variation in student responses in elementary schools. Specifically through learning methods, adjustments to learning media, differentiated learning, and the role of Catholic Religious Education teachers in strengthening and guiding students. The method used is a descriptive method with a literature study approach that includes data collection and analysis of various journals, scientific articles, and books relevant to this research topic. The study’s findings indicate that the application of a variety of learning methods, the adaptation of various learning media, and the application of differentiated learning can increase student motivation, participation, and varying levels of understanding, depending on their learning characteristics. Furthermore, Christian Religious Education teachers play a crucial role not only in the cognitive aspect but also in fostering faith, character, and other Christian values. Therefore, adapting learning strategies by teachers is crucial in supporting the overall development of elementary school students and creating a student-centered learning environment.